Effects of tibiofemoral compression on ACL forces and knee kinematics under combined knee loads. Issue 3 (27th February 2019) - Markolf, Keith; Yamaguchi, Kent; Matthew, Justin; McAllister, David
ABSTRACT: Injuries to the anterior cruciate ligament (ACL) can occur during landing from a jump or changing direction during a cutting maneuver. In these instances, the knee is subjected to combined forces and moments as it flexes under tibiofemoral compression force (TCF). We hypothesized that TCF would increase ACL forces and tibiofemoral motions under isolated and combined modes of loading relevant to knee injury. ACL force and knee kinematics were recorded in human cadaveric specimens during knee flexion from 0° to 50° under the following test conditions (alone and in combination): 2 N‐m internal tibial torque (IT), 5 N‐m valgus moment (VM), and 45N anterior tibial force (AF). Knees were tested with 25N (baseline), 250N, and 500N TCF. ACL force increased with knee flexion during all tests. As the knee was flexed, VM produced a coupled internal tibial rotation, and IT produced a coupled valgus rotation. ACL forces with IT + VM were significantly higher than with IT alone (beyond 10° flexion) or VM alone (at all flexion angles). Increasing the level of TCF above baseline did not significantly change valgus or tibial rotations for any loading condition, but did significantly increase anterior tibial translation (ATT) at all flexion angles and ACL force at flexion angles beyond 5° to 15°. Addition of AF to tests with IT + VM significantly increased ATT and ACL force without significantly altering internal and valgus rotations. The mechanism of high ACL force generation from increased TCF was related to ATT and not internal or valgus rotations of the tibia. © 2019 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res